(untitled) (Bangladesh Heart Journal, 2017)
Hypertension is one and the major non communicable diseases in the world and contributing significantly to the burden of cardiovascular diseases, stroke, kidney failure and premature death. The prevalence of hypertension in Bangladesh varies from 11- 20% and 7% of the death in Bangladesh are due to hypertension related disease. Only 11% of the total cases of hypertension have effective control of blood pressure. Education, social awareness, income, access to physicians may be factors for less adherences to medications and effective control of the disease. This study was undertaken in a group of population with average to good educational, social and economic background to see the incidence of the disease, its control and associated cardiovascular and metabolic status. 599 working officials above the age of 50 years were evaluated in BIRDEM General Hospital from January 2013 to December 2013 to see the incidences of hypertension, control of blood pressure and cardiac and metabolic status of the population. Total 308 patients in the study population had hypertension and 39 were newly detected. 68.8% of the patients with hypertension have effective control of blood pressure with medications and systolic hypertension was revealed in 8.7% cases. This might be due to increase awareness of the study population related to the educational, economic and social background and this plays an important role in effective control of the disease. Bangladesh Heart Journal 2016; 31(2) : 52-57